2017
DOI: 10.5114/aoms.2016.59713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel ascorbate-based protocol on infarct size and ventricle function in acute myocardial infarction patients undergoing percutaneous coronary angioplasty

Abstract: IntroductionThis study was designed to test the hypothesis that high-dose ascorbate prior to reperfusion followed by low chronic oral doses ameliorate myocardial reperfusion injury (MRI) in acute myocardial infarction patients subjected to primary percutaneous coronary angioplasty (PCA).Material and methodsA randomized double-blind placebo-controlled and multicenter clinical trial was performed on acute myocardial infarction (AMI) patients who underwent PCA. Sodium ascorbate (320 mmol/l, n = 53) or placebo (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…In the clinical setting, impaired micro-circulatory reperfusion was improved by ascorbate infusion in patients undergoing elective PCA[ 74 ]. Similar results were recently reported by our group[ 75 ]. These results suggest a positive role of antioxidants in counteracting the deleterious effects of oxidative stress on microvascular function.…”
Section: Role Of Antioxidantssupporting
confidence: 93%
See 1 more Smart Citation
“…In the clinical setting, impaired micro-circulatory reperfusion was improved by ascorbate infusion in patients undergoing elective PCA[ 74 ]. Similar results were recently reported by our group[ 75 ]. These results suggest a positive role of antioxidants in counteracting the deleterious effects of oxidative stress on microvascular function.…”
Section: Role Of Antioxidantssupporting
confidence: 93%
“…Our group recently developed a randomized clinical trial in patients with AMI undergoing PCA, where massive doses of ascorbate (or placebo) were administered prior to PCA. Patients treated with ascorbate prior to myocardial reperfusion showed a better recovery of ejection fraction at 2-3 mo (measured by cardiac magnetic resonance) and significantly higher myocardial perfusion after PCA ( TIMI -myocardial perfusion grade) than placebo patients, with no differences in infarct size[ 75 ] (Table 1 ).…”
Section: Role Of Antioxidantsmentioning
confidence: 99%
“…One recent randomized multicenter clinical trial on patients with myocardial infarction undergoing percutaneous coronary angioplasty did not show a significant improvement in infarct size or ejection fraction at the time of the intervention with vitamin C administration. However, a decline in the LVEF between 7-15 d and 2-3 mo noted in the control group was not seen in the vitamin C group[ 63 ]. The authors of this study suggested that vitamin C may have ameliorated myocardial reperfusion injury[ 63 ].…”
Section: Vitamin C In Cardiovascular Patientsmentioning
confidence: 99%
“…However, a decline in the LVEF between 7-15 d and 2-3 mo noted in the control group was not seen in the vitamin C group[ 63 ]. The authors of this study suggested that vitamin C may have ameliorated myocardial reperfusion injury[ 63 ].…”
Section: Vitamin C In Cardiovascular Patientsmentioning
confidence: 99%
“…The biologic plausibility of the cardioprotective effect of VC has been shown in clinical trials where VC reduced ROS when administered prior to PCI [33,34,42,43]. However, the outcomes are conflicting, with some studies showing reduction of the biomarkers of myocardial injury cTnI and CK-MB [39,41], whereas others fail to show a benefit [29,44]. Given these inconsistences, it is prudent to address the question whether or not VC administration is benefits following PCI.…”
Section: Introductionmentioning
confidence: 99%